Aktivitas Belajar dan Kemampuan Pemecahan Masalah Matematika dengan Menggunakan Model Means Ends Analysis (MEA) pada Siswa Kelas VIII MTsN 6 Agam Tahun Pelajaran 2022/2023 - Tri Novika, Ranti (Science and Education Journal (SICEDU), 2023)
This study aims to find out how the learning activities of students who follow the MEA model and whether the mathematical problem solving abilities of students who follow the MEA model are higher than students who take conventional learning. The type of research is a pre-experimental study with the static group comparison design. The population in this study were all students of class VIII MTsN 6 Agam, totaling 270 students. The instruments in this study were observation sheets of learning activities and tests of students' mathematical problem solving abilities. From the results of analysis of student learning activity data showing active criteria with an average of 61.94%, and also analysis of data on tests of students' mathematical problem solving abilities using the t-test obtained tcount = 2.60 > ttable = 1.67, so H0 is rejected . For Minitab software testing at the significance level α = 0.05, a P-value = 0.006 is obtained, meaning that the P-value <α, therefore H0 is also rejected. finally it can be concluded that students' mathematics learning activities by following the MEA learning model in class VIII students of MTsN 6 Agam are classified as active and the mathematical problem solving abilities of students who follow the MEA model are higher than students who take conventional learning in class VIII MTsN 6 Agam in the 2022/2023 academic year.